UNIVERSALITAS DAN RELATIVITAS HAM - Ikhwan Matondang (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2008)
Abstract: Universality and Relativity of Human Rights. Different approaches to human rights result in two principal theories of universalistic and relativist. The first contends that human rights are integral part of human existence regardless of time and place. Human rights are solely based on the very fact of human existence. The latter theory contends that human beings are product of their life contexts, therefore human rights should also be considered in the lights of socio-cultural backgrounds. Cultural differences results in differences on ideas and realities while maintaining the universal substances of human rights.Kata Kunci: HAM, universalitas, relativitas